Gene Transfer in Animals - Shrestha, Tilak R. (Tribhuvan University Journal, 2010)
Available with fulltext. Key words: Genes; Animals; Microinjection Tribhuvan University Journal Vol. XIX, 1996 Page: 59-71 Uploaded Date: 24 Nov., 2010